Symbol-error probability and bit-error probability for optimum combining with MPSK modulation - Debang Lao; Haimovich, A.M. (IEEE transactions on communications, 2004)
New expressions are derived for the exact symbol error probability and bit-error probability for optimum combining with multiple phase-shift keying. The expressions are for any numbers of equal-power cochannel interferers and receive branches. It is assumed that the aggregate interference and noise is Gaussian and that both the desired signal and interference are subject to flat Rayleigh fading. The new expressions have low computational complexity, as they contain only a single integral form with finite limits and finite integrand.